New 5-Aryl-1,3,4-Thiadiazole-Based Anticancer Agents: Design, Synthesis, In Vitro Biological Evaluation and In Vivo Radioactive Tracing Studies - Rana M. El-Masry; Basma M. Essa; Adli A. Selim; Soad Z. El-Emam; Khaled O. Mohamed; Tamer M. Sakr; Hanan H. Kadry; Azza T. Taher; Sahar M. Abou-Seri (MDPI AG, 2022)
A new series of 5-(4-chlorophenyl)-1,3,4-thiadiazole-based compounds featuring pyridinium (3), substituted piperazines (4a-g), benzyl piperidine (4i), and aryl aminothiazoles (5a-e) heterocycles were synthesized. Evaluation of the cytotoxicity potential of the new compounds against MCF-7 and HepG2 cancer cell lines indicated that compounds 4e and 4i displayed the highest activity toward the tested cancer cells. A selectivity study demonstrated the high selective cytotoxicity of 4e and 4i towards cancerous cells over normal mammalian Vero cells. Cell cycle analysis revealed that treatment with either compound 4e or 4i induced cell cycle arrest at the S and G2/M phases in HepG2 and MCF-7 cells, respectively. Moreover, the significant increase in the Bax/Bcl-2 ratio and caspase 9 levels in HepG2 and MCF-7 cells treated with either 4e or 4i indicated that their cytotoxic effect is attributed to the ability to induce apoptotic cell death. Finally, an in vivo radioactive tracing study of compound 4i proved its targeting ability to sarcoma cells in a tumor-bearing mice model.